Progressive familial intrahepatic cholestasis type 4 in an Indian child: presentation, initial course and novel compound heterozygous mutation. Issue 7 (6th July 2020) - Mirza, Nida; Bharadwaj, Ravi; Malhotra, Smita; Sibal, Anupam
Abstract : A 15-year-old boy who had a history of on and off pruritus and jaundice since many years found to have a novel mutation in TJP2 gene. On examination, he had clubbing, splenomegaly, grade 3 oesophageal varices and short stature. Investigation revealed direct hyperbirubinemia with elevated liver enzymes with normal gamma-glutamyl transferase (GGT). Antinuclear antibody (ANA), smooth muscle antibody (SMA) anti-liver kidney microsomal (anti-LKM) and viral markers for hepatitis were negative. However, IgG was elevated and anti-smooth muscle antibody (ASMA) was weekly positive (1:20). He was also given a trial of steroid and azathioprine for 1 year on the basis of liver biopsy findings, raised IgG and positive ASMA but finding no improvement stopped. Genetic testing by next-generation sequencing found a novel compound heterozygous missense variation in exon 17 of the TJP2 gene confirming progressive familial intrahepatic cholestasis type 4 as the aetiology of cholestatic liver disease.